Community-Based Psychoeducational Services for Strengthening Emotional Regulation and Optimism among Elementary School Students in Post-Landslide North Toraja - Imron Burhan; Musfirah Musfirah; Miftahul Jannah; Naufal Qadri Syarif; Iyan Iyan (Help: Journal of Community Service, 2026)
This community service program aimed to strengthen emotional regulation and optimism among elementary school students in post-landslide North Toraja through community-based psychoeducational services. Children are among the most vulnerable groups affected by natural disasters, often experiencing emotional distress, anxiety, and diminished hope for the future. The program was conducted at SDN 3 Buntao, North Toraja, on 21–22 July 2025 and involved students, teachers, parents, and community representatives. The implementation consisted of three stages namely preparation, implementation, and reflection. During the preparation stage, psychological needs assessments were conducted through discussions with teachers and local community members, followed by the development of culturally responsive psychoeducational materials incorporating Torajan values of mutual cooperation, kinship, and communal solidarity. The implementation stage employed participatory methods including interactive lectures, storytelling, emotional expression games, relaxation exercises, and collaborative group activities involving both students and community stakeholders. The reflection stage focused on evaluating participants’ responses and developing sustainable school–community support mechanisms. The results indicated improvements in students’ emotional awareness, emotional regulation skills, self-confidence, and optimistic attitudes toward the future. Teachers and community members also demonstrated increased awareness of the importance of psychosocial support in post-disaster recovery. These findings suggest that community-based psychoeducational services provide an effective and culturally relevant approach to strengthening children’s psychological resilience in disaster-affected areas.